NOX family NADPH oxidases in liver and in pancreatic islets: a role in the metabolic syndrome and diabetes?. (19th September 2008) - Guichard, Cécile; Moreau, Richard; Pessayre, Dominique; Epperson, Terry Kay; Krause, Karl-Heinz
Abstract : The incidence of obesity and non-esterified ('free') fatty acid-associated metabolic disorders such as the metabolic syndrome and diabetes is increasing dramatically in most countries. Although the pathogenesis of these metabolic disorders is complex, there is emerging evidence that ROS (reactive oxygen species) are critically involved in the aberrant signalling and tissue damage observed in this context. Indeed, it is now widely accepted that ROS not only play an important role in physiology, but also contribute to cell and tissue dysfunction. Inappropriate ROS generation may contribute to tissue dysfunction in two ways: (i) dysregulation of redox-sensitive signalling pathways, and (ii) oxidative damage to biological structures (DNA, proteins, lipids, etc.). An important source of ROS is the NOX family of NADPH oxidases. Several NOX isoforms are expressed in the liver and pancreatic β-cells. There is now evidence that inappropriate activation of NOX enzymes may damage the liver and pancreatic β-cells. In the context of the metabolic syndrome, the emerging epidemic of non-alcoholic steatohepatitis is thought to be NOX/ROS-dependent and of particular medical relevance. NOX/ROS-dependent β-cell damage is thought to be involved in glucolipotoxicity and thereby leads to progression from the metabolic syndrome to Type 2 diabetes. Thus understanding the role of NOX enzymes in liver and β-cell damage should lead to an increased understanding of pathomechanisms in the metabolic syndrome and diabetes and may identify useful targets for novel therapeutic strategies.